Coupling thin layer chromatography with mass spectrometry for detection and identification of sertraline and its metabolite in the urine - S. B. Baiurka; S. A. Karpushyna; N. M. Kosmina; L. V. Krichkovskaya; I. Ye. Bylov; O. O. Altukhov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
The aim of the study was to detect sertraline and its metabolites in urine under standardized thin layer chromatography (TLC) screening conditions and identify the metabolites using the mass spectrometry method.